2005
DOI: 10.1002/cncr.20776
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of irinotecan plus celecoxib in adults with recurrent malignant glioma

Abstract: BACKGROUND In the current study, the authors report a Phase II trial of irinotecan (CPT‐11), a topoisomerase I inhibitor active against malignant glioma (MG), with celecoxib, a selective COX‐2 inhibitor, among MG patients with recurrent disease. METHODS Patients with MG at any type of recurrence received CPT‐11, administered as a 90‐minute intravenous infusion on Weeks 1, 2, 4, and 5 of each 6‐week cycle plus celecoxib, which was administered continuously at a dose of 400 mg twice a day. CPT‐11 was given at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 49 publications
3
62
0
1
Order By: Relevance
“…Prior therapy consisted of surgery, radiotherapy, and chemotherapy in 12 participants (75%); surgery and radiotherapy in 3 participants (18.7%); and radiotherapy and chemotherapy in one participant (6.3%) with biopsy-proven glioblastoma multiforme. The median time from diagnosis to treatment was 14.5 months, and the median tumor volume treated was 14.45 cm 3 . Based on postoperative imaging, catheter placement was optimized in 2 participants without altering the treatment protocol.…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior therapy consisted of surgery, radiotherapy, and chemotherapy in 12 participants (75%); surgery and radiotherapy in 3 participants (18.7%); and radiotherapy and chemotherapy in one participant (6.3%) with biopsy-proven glioblastoma multiforme. The median time from diagnosis to treatment was 14.5 months, and the median tumor volume treated was 14.45 cm 3 . Based on postoperative imaging, catheter placement was optimized in 2 participants without altering the treatment protocol.…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
“…Furthermore, recurrence is typically accompanied by progressive physical and cognitive debilitation. 3 As a result, 2 secondary outcome measures have emerged in neurooncology trials: evaluations of neurocognitive function (NCF) and quality of life (QoL).…”
mentioning
confidence: 99%
“…Similarly, ACNU, another nitrosourea given alone or in combination with teniposide or cytarabine in patients with GBM after TMZ failure resulted in limited activity and considerable toxicity [69]. The combination of CPT-11 and celecoxib, a selective COX-2 inhibitor was well tolerated and had a marginal activity against heavily pretreated recurrent glioma (mostly GBM) patients with PFS6 of 25.1% [70].…”
Section: Other Irinotecan-based Combinationsmentioning
confidence: 99%
“…One of the newer drugs that have been used in recurrent glioma is irinotecan (Camptosar, Pfizer Pharmaceuticals), a topoisomerase I inhibitor with good penetration of the blood-brain barrier. Several clinical trials were conducted and showed response rates from 2.2% to 16% (37,50,51). Progression-free survival after 6 months was reported to be 25% to 43% in some studies (50,51).…”
Section: Current Therapeutic Options For Glioblastomamentioning
confidence: 99%
“…Several clinical trials were conducted and showed response rates from 2.2% to 16% (37,50,51). Progression-free survival after 6 months was reported to be 25% to 43% in some studies (50,51). More recently, antiangiogenic compounds were reintroduced into the therapeutic field of recurrent malignant glioma.…”
Section: Current Therapeutic Options For Glioblastomamentioning
confidence: 99%